Cis-acting modifiers in the ABCA4 locus contribute to the penetrance of the major disease-causing variant in Stargardt disease - Lee, Winston; Zernant, Jana; Nagasaki, Takayuki; Molday, Laurie L; Su, Pei-Yin; Fishman, Gerald A; Tsang, Stephen H; Molday, Robert S; Allikmets, Rando (Human molecular genetics, 2021)
Abstract Over 1200 variants in the ABCA4 gene cause a wide variety of retinal disease phenotypes, the best known of which is autosomal recessive Stargardt disease (STGD1). Disease-causing variation encompasses all mutation categories, from large copy number variants to very mild, hypomorphic missense variants. The most prevalent disease-causing ABCA4 variant, present in ~ 20% of cases of European descent, c.5882G > A p.(Gly1961Glu), has been a subject of controversy since its minor allele frequency (MAF) is as high as ~ 0.1 in certain populations, questioning its pathogenicity, especially in homozygous individuals. We sequenced the entire ~140Kb ABCA4 genomic locus in an extensive cohort of 644 bi-allelic, i.e. genetically confirmed, patients with ABCA4 disease and analyzed all variants in 140 compound heterozygous and 10 homozygous cases for the p.(Gly1961Glu) variant. A total of 23 patients in this cohort additionally harbored the deep intronic c.769-784C > T variant on the p.(Gly1961Glu) allele, which appears on a specific haplotype in ~ 15% of p.(Gly1961Glu) alleles. This haplotype was present in 5/7 of homozygous cases, where the p.(Gly1961Glu) was the only known pathogenic variant. Three cases had an exonic variant on the same allele with the p.(Gly1961Glu). Patients with the c.[769-784C > T;5882G > A] complex allele exhibit a more severe clinical phenotype, as seen in compound heterozygotes with some more frequent ABCA4 mutations, e.g. p.(Pro1380Leu). Our findings indicate that the c.769-784C > T variant is major cis-acting modifier of the p.(Gly1961Glu) allele. The absence of such additional allelic variation on most p.(Gly1961Glu) alleles largely explains the observed paucity of affected homozygotes in the population.